JERAMI SEBAGAI BAHAN BAKU PANEL AKUSTIK PELAPIS DINDING (DIMENSI: Journal of Architecture and Built Environment, 2009)
The demand of walling panels with acoustic qualification has surprisingly increased, due to the needs for home theaters and mini recording studios in the increase of environmental noise. Therefore, good supply of acoustic panels, especially those with lower price are necessary. A series of study to explore possibility in using paddy-straw as main material to construct cheap and high quality panels has been developed. Prior to this study, an earlier small research showed there was a great potency in using paddy-straw as panels, especially ones drawn from paddy in type IR. The earlier study recommends further research to examine strength of compression and tensile of the constructed panels to go for building materials, which is presented in this paper. Acoustic qualification of the panels is subject for further reserach.Abstract in Bahasa Indonesia:Kebutuhan akan panel pelapis dinding yang bersifat akustik terus meningkat seiring meningkatnya kebisingan dan kebutuhan terhadap ruang studio pribadi. Ketersediaan panel pelapis dinding dengan harga yang lebih terjangkau seperti yang terbuat dari bahan limbah sangatlah dibutuhkan. Pada penelitian awal telah diselidiki kemungkinan penggunaan jerami yang merupakan limbah sebagai bahan baku pembuatan panel akustik. Penelitian tersebut menunjukkan bahwa jerami sangat potensial digunakan sebagai bahan aku panel, terutama jerami padi berjenis IR. Selanjutnya panel jerami ini perlu mendapatkan perlakukan uji desak dan lentur untuk memastikan kemampuannya menahan berat sendiri dan kekuatannya saat proses penggunaan, sebelum akhirnya mengalami pengujian berkaitan dengan kualitas akustik. Kekuatan desak dan lentur panel dimaksud, tersaji dalam tulisan ini.Kata kunci: panel jerami, uji desak, uji lentur.